Controlling the Double Layer of Platinum by Selective Passivation of Step Sites Using Adatom Modification - Nicci L. Fröhlich; Yifan Hu; Alfred Larsson; Marc T. M. Koper (Journal of the American Chemical Society, 2026)
Abstract The structure of the electric double layer at platinum electrodes remains incompletely understood, even for the model Pt(111)/HClO4 interface, which deviates significantly from Gouy–Chapman–Stern theory. While Pt(111) exhibits a true double-layer window (0.40–0.60 VRHE) that enables direct measurement of the double-layer capacitance, stepped Pt surfaces do not because hydrogen and/or hydroxyl species adsorb at low-coordinated step sites across the entire potential range. We previously showed that hydroxyl adsorption on (110)-steps is potential-independent within this nominal double-layer window, leading to decreasing capacitance with increasing (110)-step density due to suppression of the step Helmholtz capacitance. In contrast, (100)-steps exhibit potential-dependent hydroxyl adsorption that introduces a substantial pseudocapacitive contribution and increases capacitance with step density. Here, we selectively passivate Pt step sites by depositing Au* and Ag* adatoms. We find that Au*step-modification suppresses step-specific adsorption, restoring predominantly electrostatic behavior for (100)-type stepped Pt surfaces and reversing the capacitance trends observed for the bare stepped surfaces. In contrast, Ag*step-modification introduced an additional chemical contribution, manifested as substantially increased capacitance and enhanced CO oxidation activity due to adsorption of oxophilic species on Ag*. These results demonstrate that Pt step-site chemistry, and consequently the electrical double-layer structure and electrocatalytic activities, can be tuned and probed to a remarkable degree of controllability through selective adatom modification.